(3TQM GdebGdGJ GdBQHY dHWdjehSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s; (3HWdjehS GdMcje GdbdhPjs ((3eMeO Hf YHO Gddg GdTLGYi s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3bUOfG Cf TQM CbGhjd GdMcje HWdjehS s
(3BNQgG (B:s
(3agPg CTjGA bO TQMJgG dc eG fYe GdfXQ ajgG hJCedgG hGddg jgOi ef jTGA s
(3cJGH GdbVGA HGdfLhe Ydi GdMhGOKs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs